ANALISIS KEPENTINGAN DAN KINERJA ATRIBUT PELAYANAN PADA WARUNG MAKAN IBU IIS DI BANDAR LAMPUNG - Alfina Ulfami; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
Warung Makan Ibu Iis is the target of this research, which seeks to examine critical features, performance attributes, and maintenance and improvement needs. A survey approach utilized to gather data from the research location. This research employed  quota and non-probability sampling methods to compile a sample size of 64 individuals. The data collection was conducted in November 2023.  To analyze the data, this research used Importance Performance Analysis (IPA). The findings  of the research related to attribute performance of service at Warung Makan Bu Iis indicated that menu variety and parking availability were  two areas that  need some improvement. In addition, the feature that customers rank as having the lowest performance level was  menu variety, with a score of 4.41, while the attribute that has the best ranks  was the comfortableness of the venue, which rated about  4.56.   Key words:   Attributes, Importance, IPA, Performance, Warung Makan